THE FORMATION OF INTELLECTUAL AND SPIRITUAL INTELLIGENCE OF STUDENTS IN THE ERA OF ADVANCED SCIENCE AND TECHNOLOGY WITH T2R INNOVATION - Mochammad Ricky Rifa'i; Rivo Alfarizi Kurniawan; Bagus Pramono (UIN Sumatera Utara Medan, 2020)
So far, various problems that occur in schools are very alarming. This problem is a concern for the general public, especially for parents and teachers. The rapid development of modern science and technology has become one of the causes. The purpose of this study is to determine the formation of intellectual and spiritual intelligence through T2R innovation. In Al-Qur'an, the Ali 'Imron verses 190-191 contains the concept of the balance of human thought patterns and contemplation of the heart which is translated in the order of intellectual and spiritual intelligence. Intellectual intelligence is related to the awareness of space, something that appears, and the mastery of mathematics. Spiritual intelligence deals with and solves problems of meaning and wider values. The method used in this research is study library research (SLR) and interviews with data processing techniques in the form of descriptive analysis. The T2R innovation is designed to be a solution related to the problems that occur, namely by conducting innovation teaching orientation, ta'lim muta'allim implementation, and improving the world scientific research.